Facile Size‐Controllable Synthesis of Colorful Quasi‐Cubic α‐Fe2O3 Materials from Nanoscale to Microscale and Their Properties Related to the Size Effect. Issue 8 (28th June 2013) - He, Shuai; Wang, Guang‐Sheng; Wang, Jia‐Wei; Wei, Yun‐Zhao; Wu, Yun; Guo, Lin; Cao, Mao‐Sheng
Abstract A facile and environmentally friendly hydrothermal approach has been employed to synthesize size‐controllable quasi‐cubic α‐Fe2O3 nanocrystals by using an aqueous solution of FeCl3 without any alkaline materials and stabilizing agent. The as‐prepared products were carefully characterized and the growth mechanism is also discussed. This hydrothermal synthesis of such quasi‐cubic structures implies a simple and low‐cost route to prepare monodisperse nanomaterials on a large scale. The size‐controllable synthesis of α‐Fe2O3 is the first achieved successfully from 80 nm to 2 μm with constant structures. The synthesized α‐Fe2O3 materials have different optical properties and stabilities in water, which are caused by the change of their band‐gap energy and specific surface areas. Finally, the dielectric properties of synthesized α‐Fe2O3 cubes were also investigated, and the differences caused by the particle sizes are discussed.